Exploration of the Joint Teaching Model of Tomographic-radiologic Anatomy and Topographic Anatomy in A Way of Case-based Learning - ZHAO Qing; LIU Wei; ZHANG Hongmei; ZHAO Xinming; ZHOU Chunwu (Xiehe Yixue Zazhi, 2024)
ObjectiveTo explore how the joint-teaching mode of tomographic-radiologic anatomy and topographic anatomy in a way of case-based learning (CBL) promotes the education of medical students.MethodsAccording to the principle of systematic random sampling, the students of the eight-year pilot class of clinical medicine and the graduate students majoring in medical imaging were randomly assigned to the joint teaching group and the control group. They respectively received the joint-teaching of tomographic and topographic anatomy based on CBL and the traditional teaching of topographic anatomy. At the end of the course, both groups of students had a theoretical knowledge test and a course evaluation.ResultsA total of 68 students were recruited in this study, including 39 students from the 2022 grade of eight-year pilot class of clinical medicine in Peking Union Medical College and 29 first-year master students majoring in medical imaging. There were 34 students in the joint teaching group (20 from the 8-year pilot class and 14 from the master's program) and 34 students in the control group (19 from the 8-year pilot class and 15 from the master's program). The average knowledge test scores and course evaluation scores in the four dimensions of "improving the mastery of anatomy knowledge", "improving the interest in anatomy", "improving the recognition of radiologic knowledge", and "improving the clinical comprehensive ability" were significantly higher in the joint teaching group than in the control group (all P < 0.05). In the subgroup analysis, the average knowledge test scores of the students from the 8-year pilot class and master's program in the joint teaching group were respectively higher than those in the control group. In addition, joint teaching could significantly improve the radiologic cognition and comprehensive clinical ability of the students from the 8-year pilot class, while students from the master's program may benefit more in anatomy knowledge and clinical application.ConclusionsThe case-based joint-teaching mode can promote the mastery of anatomy knowledge, radiologic cognition and comprehensive clinical ability of medical students from different academic systems.